Studies on biodiesel production from DDGS-extracted corn oil at the catalysis of Novozym 435/super absorbent polymer. (15th April 2015) - Gu, Jiahui; Xin, Zhong; Meng, Xin; Sun, Shuzhen; Qiao, Qingan; Deng, Hongbo
Abstract : Graphical abstract: Operational stability of pure Novozym 435 and Novozym 435/SAP. Highlights: Transestertification of DMC and oil with high acid value and high water content. The reaction route and reaction mechanism of the DMC and FFA were speculated. Evaluating of different water absorbents on the yield of biodiesel. Novozym 435/SAP showed great catalytic activity and operational stability. Novozym 435/SAP is easy to be recycled and can be used in fixed bed reactor. Abstract: The corn oil extracted from distillers dried grains with solubles (DDGS), which has a high acid value of 41.6 mg KOH/g and a high water content of 4.5%, is used to produce biodiesel in this article. The transesterification of dimethyl carbonate (DMC) and DDGS-extracted corn oil was studied at the catalysis of Novozym 435. Meanwhile, several water removal agents, which include acrylic super absorbent resin (SAP), 4A-molecular sieve, blue silica-gel and tert-butanol, were added to absorb the water during the reaction. The yield of fatty acid methyl esters (FAMEs) was analyzed by GC with internal standard method. The effect of different reaction conditions (type of water absorbent, molar ratio of DMC to oil, reaction time and temperature, lipase and SAP amount) on the yield of FAMEs were also discussed. Then the highest yield of FAMEs could reach 91.0% at 60 °C for 18 h with molar ratio of DMC to oil 15:1, Novozym 435 amount of 20 wt% and SAP amount of 10 wt% (based on the oil mass). Finally, Novozym 435/SAP showed excellent operational stability without losing any catalytic activity after 8 cycles of repeated use, and the water absorbed by Novozym 435/SAP can be dried at mild temperature (60 °C). Because it is easy to be recycled, the Novozym 435/SAP has a great potential to be used in the continuous biodiesel apparatus such as the fixed bed reactor.